Modern geoelectromagnetic researches of the Ukrainian Carpathians - Burakhovych, T.; Kushnir , A.; Ilienko, V. (Geofizicheskiy Zhurnal, 2022)
Based on the results of modern synchronous geoelectromagnetic studies, a spatiotemporal picture of the distribution of geomagnetic variations and the electric field on the Earth’s surface, as well as an idea of the distribution of electrical conductivity and the geoelectric structure of the subsurface section of the southwestern Ukrainian Carpathians, was obtained. The experimental data were processed using the PRC_MTMV software package; the properties of response functions — tippers for periods of geomagnetic variations from 50 to 5000 s and curves of apparent electrical resistivity (amplitude values and impedance phases) from 10 to 1000 s were analyzed. The anomalies of electrical conductivity in the Earth’s crust outlined as a result of a qualitative interpretation correspond to fault tectonics and create a chain of four local differently oriented sections, the common axis of which runs between the Transcarpathian and Chernogolovsky deep faults, and in the southern part between the latter and Uzhotsky (it is also possible to consider the option of a single longitudinally heterogeneous conductive structure within the concept of the axial zone of the Carpathian magnetovariational anomaly). An inhomogeneous distribution of electrical conductivity at the depths of the upper mantle was recorded in the Ukrainian Carpathian region from the Transcarpathian trough to the Skibov cover. It is shown that there is a general northeastern deepening of the upper edge from 40—60 km (Transcarpathian trough) to 90—100 km (Krosnensky cover) and its sharp subsidence in the zone of the Porkuletsky and Duklyansky covers. Three sections were distinguished along the strike of the inner and central zones of the Outer Carpathians: the northern one is characterized by a deepening of the upper edge and a branching of electrical conductivity along the depth towards the south; The obtained results of geoelectromagnetic studies are in good agreement with geothermal zoning, correspond to the structure of the lithosphere according to the DSS profiles and with ideas about the geodynamic development of the interior.